A physiologically-based flow network model for hepatic drug elimination III: 2D/3D DLA lobule models - Rezania, Vahid (My University, 2016)
Recently, we developed a physiologically-based lattice model to address the transport and metabolism of drugs in the liver lobule (liver functional unit). In this paper, we extend our idealized model to consider structural and spatial variability in two and three dimensions.
Keywords: liver lobules; drugs